A study on how basic psychotherapy training is perceived by Swedish physicians in psychiatry. Issue 4 (4th July 2019) - Johansson, Per Magnus; Fahlke, Claudia
ABSTRACT: In Sweden, physicians training to be psychiatrists must complete a basic course in psychotherapy. This study investigated the perceptions of this course by 18 physicians who completed a basic course in psychotherapy. All participants answered a paper-and-pencil questionnaire and four were also interviewed. The results show that most physicians were satisfied with the course, especially with its focus on different psychotherapeutic perspective that gave them the opportunity to train in both cognitive behavioural therapy and psychodynamic therapy. Continuing to offer physicians high-quality psychotherapy training, especially one that encourages knowledge of several theories and methods that will later be useful in clinical practice as a psychiatrist, will benefit future psychiatrists and their patients.